Capacity of the Nearby Infrared Spectroscopy (NIRS) Red for the Prediction of some Properties of Burned Soils in a Semi-Arid Area of Western Algeria - Borsali Amine Habib; Bénabdéli Khéloufi; Gros Raphaël (Journal of Basic & Applied Sciences, 2014)
The forestry sector in Algeria is confronted for the years 1965 to a resurgence of the fires that destroy averaged 48 000 ha per year, or 12% of forest areas. As a result of repeated fires, a pyrophyte vegetation develops on degraded soils and from which the spontaneous regeneration of forest stands and reforestation are very difficult. The Algerian forest sustainable management must therefore be informed by an assessment of the physico-chemical quality of burned soils and the vulnerability of microbial activities in this disturbance Any rehabilitation or regeneration of the burned forest ecosystems program must take into consideration the impact of the fires on the ground [1] and therefore evaluate a large number of soil properties [2]. The main objective of this study was to evaluate the ability of spectroscopy in the near infra-red to predict the time since the last fire and burned some microbiological characteristics of soil. This study is interested in the pine forests of the Algerian semi arid floor Aleppo pines. Promising results have shown a prediction rather senssible of the time since the last fire. The advantages of the SPIR are many. This method is fast, inexpensive and non-destructive.